Editorial: Public Perception of the Health Profession (The East and Central African Journal of Pharmaceutical Sciences, 2018)
In a preface to the play 'The Doctor Dilemma', the Irish poet/play writer George Bernard Shaw (GBS) wrote "All professions are a conspiracy against the laity'. GBS was a Nobel laureate in 1925 and a cofounder of the London School of Economics. His comments, though meant to amuse, mirrored the opinion of the general public. Others have made similar uncomplimentary humorous comments. For example psychiatrists are accused of levying tax on those who build castles in the air (psychopaths) and collecting tax from those who live in them (schizophrenics). Away from the prying eyes of general public and comedians, there is a lot of serious introspection by health professionals and where possible remedial corrective measures are undertaken. Simply put, the professionals are not immune to genuine public criticism. A Google search of 'public perception of doctors' in early 2014 returned 17,700,000 results. Corresponding searches for nurses, dentists and pharmacists returned 7,750,000, 871,000 and 1,220,000 results, respectively. Many of the research articles are published in peer reviewed scholarly journals. The researchers used open-ended and closed format questionnaires and met all the requirements for credible scientific research. In the past, this journal has published articles on public perception of pharmacists, the representative samples being obtained from patients attending outpatient clinics
Keywords: HEALTH PROFESSION; PUBLIC